Foreign Direct Investment Dynamics in South Africa: Reforms, Trends and Challenges (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2019)
This paper gives an overview of foreign direct investment (FDI) in South Africa from 1980 to 2017. It highlights trends in FDI inflows, reforms that have been implemented to date, and challenges that need to be addressed in order to increase the FDI inflows into the country. Government reforms on FDI have been two pronged. Firstly, there are policies that are aimed at creating a strong competitive industry and a strong industrial base for investment. Among such policies are trade liberalisation policies, multilateral and regional integration policies, supportive industrial policies, and bilateral trade agreements. Secondly, there are policies that directly target the FDI investment. These policies include, amongst others, investment incentives, regulatory reforms, exchange control relaxation, and Bilateral Investment Treaties (BITs) reforms. The findings from this study show that FDI inflows have increased significantly from 1990 although they still remain depressed.